The Analysis of Arabic-English Mixing Code and Switching Code on Arabic Ometv Video M.Rozi's Youtube Channel - Fahmy Lukman; Asyafa Umayah Rubawan Al-Qosam; Tajudin Nur (Center of Language and Cultural Studies, 2023)
Abstract Ometv is a platform for communication between Middle Eastern people and foreigners through video without language and geography barriers. This platform is used by YouTube creators to create content, giving birth to many creators who are bilingual or more. The process of communicating on content occurs resulting in code mixing and code switching. This research method uses a sociolinguistic approach based on Pieter Musyken's theory as well as Suwito's theory and the analysis process is carried out using a qualitative descriptive method through direct element division (BUL). This study uses 46 data contained in the Saudi Arabian version of Ometv. The data were classified into 3 categories: insert code mixing (30 data), alternation code mixing (11 data), and congruent lexicalization code mixing (5 data). As for the external code switching process, there are 46 of these data and 1 internal code switching data. The causes and functions of code mixing and code switching based on the analysis are (1) Speaker background, (2) Vocabulary Requirements, and (3) Demonstrating expression through utterances. Keywords: Ometv, mixing code, switching code, Muysken, Suwito